KDM5 demethylases and their role in cancer cell chemoresistance - Plch, Johana; Hrabeta, Jan; Eckschlager, Tomas (International journal of cancer, 2019)
Histone methylation is important in the regulation of genes expression, and thus its dysregulation has been observed in various cancers. KDM5 enzymes are capable of removing tri- and di- methyl marks from lysine 4 on histone H3 (H3K4) which makes them potential players in the downregulation of tumor suppressors, but could also suggest that their activity repress oncogenes. Depending on the methylation site, their effect on transcription can be either activating or repressing. There is emerging evidence for deregulation of KDM5A/B/C/D and important phenotypic consequences in various types of cancer. It has been suggested that the KDM5 family of demethylases plays a role in the appearance of drug tolerance. Drug resistance remains a challenge to successful cancer treatment. This review summarizes recent advances in understanding the functions of KDM5 histone demethylases in cancer chemoresistance and potential therapeutic targeting of these enzymes, which seems to prevent the emergence of a drug-resistant population.
Keywords: zvířata; Animals; chemorezistence; Humans; Histone Demethylases; Drug Resistance, Neoplasm; Neoplasms; histondemethylasy; nádory; lidé